Penanganan Kecelakan Kerja Crew di Kapal MT Pribumi - Rahman Raising; Engelberth Victory Mamusung; Rahmat Hidayat; Jamaluddin Jamaluddin; Ratnawati Raising (Yayasan Literasi Sains Indonesia, 2025)
The maritime industry carries a crucial role in the global economy, serving as the lifeline for transporting goods between countries. However, despite its vital role, the industry continues to grapple with serious work safety issues. Accidents on board ships are a persistent problem that can result in fatal consequences, ranging from severe physical injury to the loss of lives of seafarers who risk themselves at sea. The unique and often challenging working environment on board ships contributes to the complexity of these risks. This research aims to identify the factors causing work accidents on the MT Pribumi vessel and analyze strategies for addressing them. The research method used is a qualitative descriptive approach through direct observation of the crew at work, in-depth interviews with the crew and safety officers, and a literature review of previous research on maritime safety. The results show that work accidents are generally caused by a lack of compliance with safety standards, insufficient safety training, high-risk working environmental conditions, and inadequate supervision. Recommended prevention strategies include the implementation of a stricter permit to work system, the utilization of technology such as virtual reality in safety training, the improvement of safety awareness and culture, and more intensive supervision. The effective implementation of these integrated strategies is expected to significantly reduce the number of work accidents and create a safer working environment for the crew on board ships.